2016
DOI: 10.1371/journal.pntd.0004590
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Lymphatic Filariasis Data Quality in Endemic Communities in Ghana, Using the Neglected Tropical Diseases Data Quality Assessment Tool for Preventive Chemotherapy

Abstract: BackgroundThe activities of the Global Programme for the Elimination of Lymphatic Filariasis have been in operation since the year 2000, with Mass Drug Administration (MDA) undertaken yearly in disease endemic communities. Information collected during MDA–such as population demographics, age, sex, drugs used and remaining, and therapeutic and geographic coverage–can be used to assess the quality of the data reported. To assist country programmes in evaluating the information reported, the WHO, in collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 15 publications
(13 reference statements)
1
29
1
Order By: Relevance
“…Previous studies in Ghana have pointed out that data reported on epidemiological coverage may not be accurate (60%), however, this situation is not different between hotspots and stopped-MDA districts. 20 Poor compliance (44%) has been reported in a hotspot district in Ghana. 13 Secondly, although LLINs were reportedly distributed equally among the hotspot and stopped-MDA districts, there was no documentation of their actual use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Ghana have pointed out that data reported on epidemiological coverage may not be accurate (60%), however, this situation is not different between hotspots and stopped-MDA districts. 20 Poor compliance (44%) has been reported in a hotspot district in Ghana. 13 Secondly, although LLINs were reportedly distributed equally among the hotspot and stopped-MDA districts, there was no documentation of their actual use.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the fact that these reported coverage may not be very reliable [33] since some areas reported coverage more than 100% (Figure S2). Our data showed a relatively high and constant coverage over time.…”
Section: Supporting Informationmentioning
confidence: 99%
“…The number of years required to interrupt transmission appears to depend on the MF prevalence at the inception. It is important to note that several factors, in particular therapeutic coverage and adherence rates, geographical coverage [7,8], mosquito vector characteristics [9], and drug regimens [10], may all influence the rate of decline of parasitological parameters, which measure the success of the programme, will need to be considered in the process of monitoring and evaluation of MDA programmes.…”
Section: Programme Challengesmentioning
confidence: 99%
“…Furthermore, a recent study using the WHO data quality assessment (DQA) tool revealed inaccuracies of coverage results reported at the service delivery points [8], pointing to challenges in the data management and reporting tools of the programme. Therapeutic coverage and adherence to MDA are two important indices used to assess the success of MDA campaigns [19,20].…”
Section: Outlook For the Next Five Yearsmentioning
confidence: 99%
See 1 more Smart Citation